2017
DOI: 10.1159/000481845
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress Induces HRD1 to Protect Alveolar Type II Epithelial Cells from Apoptosis Induced by Cigarette Smoke Extract

Abstract: Background/Aims: Cigarette smoking is a major risk factor of chronic obstructive pulmonary disease. This study aimed to examine the effects of cigarette smoke extract (CSE) on alveolar type II epithelial cells (AECII) and investigate the underlying mechanism. Methods: Primary AECII were isolated from rat lung tissues and exposed to CSE. Apoptosis was detected by flow cytometry. Protein expression was detected by Western blot analysis. Results: Primary rat AECII maintained morphological and physiological charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 22 publications
(22 reference statements)
1
14
0
Order By: Relevance
“…In the top GO processes of increased mRNAs, autophagy identified in BP was reported to promote lung epithelial cell death, airway dysfunction in the experimental models of COPD exposed to cigarette smoke in vivo and in vitro . In addition, as a part of endoplasmic reticulum stress, IRE1‐mediated unfolded protein response was suggested involved in CSE‐induced apoptosis in alveolar type II epithelial cells . In the GO processes of decreased mRNAs, regulation of signal transduction by p53 class mediator process and extracellular matrix organisation process were identified in BP whereas histone serine kinase activity and RAGE receptor binding were found in MF, which is corresponding to the previous studies .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the top GO processes of increased mRNAs, autophagy identified in BP was reported to promote lung epithelial cell death, airway dysfunction in the experimental models of COPD exposed to cigarette smoke in vivo and in vitro . In addition, as a part of endoplasmic reticulum stress, IRE1‐mediated unfolded protein response was suggested involved in CSE‐induced apoptosis in alveolar type II epithelial cells . In the GO processes of decreased mRNAs, regulation of signal transduction by p53 class mediator process and extracellular matrix organisation process were identified in BP whereas histone serine kinase activity and RAGE receptor binding were found in MF, which is corresponding to the previous studies .…”
Section: Discussionmentioning
confidence: 99%
“…27 In addition, as a part of endoplasmic reticulum stress, IRE1-mediated unfolded protein response was suggested involved in CSE-induced apoptosis in alveolar type II epithelial cells. 28 In the GO processes of decreased mRNAs, regulation of signal transduction by p53…”
Section: Discussionmentioning
confidence: 99%
“…Some literatures showed that autophagy could augment cell apoptosis, and autophagy inhibition could reduce apoptosis [63, 64]. Most studies have shown that PM 2.5 exposure can induce autophagy, which leads to endothelial apoptosis and dysfunction [19-21, 65]. In the process of autophagy, the expression of protein 1 light chain 3I (LC3I) and protein 1 light chain 3II (LC3II) is increased, and these changes reflect the extent of the autophagy [66].…”
Section: Discussionmentioning
confidence: 99%
“…It has long been known that primary bronchial epithelial cells exposed to cigarette smoke display a transient PERK-dependent phosphorylation of eIF2α followed by induction of ATF4 and PPP1R15A [134]. Indeed, PERK-dependent eIF2α phosphorylation is a consistent feature of cells exposed to cigarette smoke or smoke extract and at least some of the cytotoxicity is mediated by ER stress-induced cell death [135,145]. For example, the aldehyde acrolein found in smoke induces ER stress-mediated cell death in A549 cells through multiple pathways including perturbed ER calcium homeostasis [146].…”
Section: Smoke and Exhaust Fumesmentioning
confidence: 99%